Cassell Dictionary of Witchcraft - Pickering, David (London Cassell, 2002)
Separating truth from myth, an expert offers an A-to-Z guide to one of the most intriguing aspects of the supernatural. Hundreds of carefully researched articles provide explanations of the key terms and concepts of witchcraft, including demons, exorcisms, familiars, the Inquisition, sabbats, shape-shifting, and spells. Fascinating biographies of key figures range from witches mentioned in the Bible and other ancient literature to the 17th-century "Witch-Finder General" Matthew Hopkins, and the modern "Great Beast," Aleister Crowley. Articles on witch trials through the centuries draw on eyewitness testimony and contemporary records of torture, confessions, and recantations. Opinions about witchcraft include legal experts, theologians, and psychologists. For example, Jean Bodin, a French philosopher, opposed the burning of witches since they usually died quickly.
Keywords: Witchcraft -- Occultism -- Parapsychology